CRITICAL ISSUES ON FORCED MIGRATION STUDIES AND THE REFUGEE CRISIS IN SOUTHEAST ASIA - Riwanto Tirtosudarmo (Jurnal Kependudukan Indonesia, 2008)
This article reviews the recent discourse on forced migration in Southeast Asia. In the aftermath of the Cold War era, movements of people have entering a new predicament. The interstate wars have produced displaced populations that many have spill into the neighboring countries or oscillating within border areas. In these new political circumstances, studies on population movement shall move beyond the conventional theoretical framework, derives from the modernization theories. The increasing magnitude of forced displacement, in many instances resulted from the state's failures in resolving political conflicts, critically challenges the conventional study on migration in which politics and security, often neglected. From a narrow academic perspective, displaced people is divided into three broad groups, based on the major cause of displacement: violent conflicts, development and natural disasters. In Southeast Asia, internal conflict that produced internally displaced population and refugees that fill or cross the state borders, is often resulted from elite's conflict or conflict between different factions in the national government, that in turn produce tensions in the society at the grassroots levels. This article argues that the need for a new perspective beyond Eurocentric framework is needed to analyze unfolding events related to migration-development-security nexus in Southeast Asia. The failure of existing international refugee regime to contain the critical issues and the refugee crises in the region mirror the failure of regional cooperation in Southeast Asia to develop a viable regional framework to tackle the problem of refugee and the displaced population.Keywords: Political conflict, force migration, regional framework